2021
DOI: 10.1155/2021/6664479
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Aftereffects of Acute tDCS Coupled with Cognitive Training: An fMRI Study in Healthy Seniors

Abstract: Enhancing cognitive functions through noninvasive brain stimulation is of enormous public interest, particularly for the aging population in whom processes such as working memory are known to decline. In a randomized double-blind crossover study, we investigated the acute behavioral and neural aftereffects of bifrontal and frontoparietal transcranial direct current stimulation (tDCS) combined with visual working memory (VWM) training on 25 highly educated older adults. Resting-state functional connectivity (rs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 52 publications
0
22
0
Order By: Relevance
“…In fact, studies that probed task‐related neural activity during application of anodal tDCS over functionally relevant brain regions have shown modulations on the network level (Holland et al, 2016 ; Martin et al, 2017 ). Investigation of changes in resting‐state networks after a single session of either anodal or bilateral tDCS over task‐relevant brain areas further demonstrated its potential to modulate functional connectivity (Meinzer et al, 2013 ; Sehm et al, 2012 ; Šimko et al, 2021 ). Indeed, anodal tDCS may induce cortical excitability changes in activated networks, as demonstrated in studies assessing transcranial magnetic stimulation‐evoked potentials using electroencephalography (Pellicciari et al, 2013 ; Pisoni et al, 2018 ; Romero Lauro et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, studies that probed task‐related neural activity during application of anodal tDCS over functionally relevant brain regions have shown modulations on the network level (Holland et al, 2016 ; Martin et al, 2017 ). Investigation of changes in resting‐state networks after a single session of either anodal or bilateral tDCS over task‐relevant brain areas further demonstrated its potential to modulate functional connectivity (Meinzer et al, 2013 ; Sehm et al, 2012 ; Šimko et al, 2021 ). Indeed, anodal tDCS may induce cortical excitability changes in activated networks, as demonstrated in studies assessing transcranial magnetic stimulation‐evoked potentials using electroencephalography (Pellicciari et al, 2013 ; Pisoni et al, 2018 ; Romero Lauro et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, while there is some evidence from single‐session tDCS studies (Meinzer et al, 2013 ; Pisoni et al, 2018 ; Sehm et al, 2012 ; Šimko et al, 2021 ), and first evidence from multi‐session tDCS studies (Antonenko, Külzow, De Sousa, et al, 2018 ; Möller et al, 2017 ) for functional network effects in human participants, whether microstructural plasticity changes accompany tDCS plus training‐related interventions is not fully understood. This knowledge on microstructural plasticity after multi‐session tDCS is crucial, however, given the potential of these approaches to induce long‐lasting neural plasticity (cf., Abellaneda‐Pérez et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the effectiveness in maintaining cognitive functions varies greatly both across and within intervention types 13 .Transcranial direct-current stimulation (tDCS) was proposed as an inexpensive and easily administered method for experimental use, and potentially also for clinical use, in an attempt to modulate cognitive functions 14 . Research aiming to modulate cognition using tDCS suggests that ongoing brain processing can be tuned and reorganized on the level of large-scale brain networks 15,16 , resulting in a favorable behavioral aftereffect via improved inter-and intra-network communication [17][18][19][20][21] . tDCS applies a weak direct electric current through two electrodes placed over the scalp with the goal of modulating underlying cortical excitability 22 .…”
mentioning
confidence: 99%
“…A decreased functional connectivity was found in left and right default modes, executive control, auditory, and attention networks in patients with MCS (33,34). Previous studies in healthy participants showed that tDCS over left DLPFC could increase the FC between the left DLPFC and bilateral parietal regions (5,35). Our findings showed that an increased FC in sensorimotor network (bilateral supplementary motor area), frontal parietal network (right angular gyrus), and auditory network (right superior temporal gyrus) post-2-week real tDCS, which provided another piece of evidence that improvement of FC in both nearby and distant of the stimulated brain regions could be induced by tDCS in patients with MCS (5,(36)(37)(38)(39).…”
Section: Discussionmentioning
confidence: 94%